2019
DOI: 10.1016/j.ijfoodmicro.2019.108356
|View full text |Cite
|
Sign up to set email alerts
|

Environmental heterogeneity of Staphylococcus species from alkaline fermented foods and associated toxins and antimicrobial resistance genetic elements

Abstract: Some of the authors of this publication are also working on these related projects:Traditional african fermented cereals View project Selection and assessment of the combination between waste of tropical fruits and probiotic strains in the modulation of intestinal microbiota of obese compared to the normal weight using the simulator of the human intestinal microbial ecosystem View project Labia Irène Ivette Ouoba Ouoba-Consulting; London Metropolitan Univesity

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 42 publications
1
17
0
Order By: Relevance
“…circulating multidrug-resistant isolated in both hospitalized, non-hospitalized patients, food and urban wastewater in Burkina Faso. These resistances (MDR, PDR and XDR) in isolates circulating in the cities of Burkina Faso could be due by the expression of resistance genes of the bla and mecA types carried by mobile and transferable genetic elements between cells of the same or different species described previously by several authors [11,13,14,37,38]. The transfer of resistance genes between isolates depends on the type of ecosystem and the mode of transfer [39][40][41][42][43].…”
Section: Discussionmentioning
confidence: 88%
“…circulating multidrug-resistant isolated in both hospitalized, non-hospitalized patients, food and urban wastewater in Burkina Faso. These resistances (MDR, PDR and XDR) in isolates circulating in the cities of Burkina Faso could be due by the expression of resistance genes of the bla and mecA types carried by mobile and transferable genetic elements between cells of the same or different species described previously by several authors [11,13,14,37,38]. The transfer of resistance genes between isolates depends on the type of ecosystem and the mode of transfer [39][40][41][42][43].…”
Section: Discussionmentioning
confidence: 88%
“…Li et al [10] reported that extra carbon sources could promote the p-chloroaniline degradation of Brevibacillus S-618 because of the cometabolism effect. Thus, some xenobiotics can promote the activities of degrading enzymes [26].…”
Section: Discussionmentioning
confidence: 99%
“…S. piscifermentans is a non-pathogenic Gram-positive that is used as part of starter cultures for fish fermentation combined with S. canosus and S. condimentii. In fermented fish product in India, S. piscifermentans has shown the capability to prevent the growth of undesirable bacteria, decrease pH, hydrogen peroxide, develop flavor and red color (Gupta et al 2018;Ouobaa et al 2019).…”
Section: Discussionmentioning
confidence: 99%